Differentiated Instruction Strategies to Support Mixed-Ability ESL Students in Academic Writing - Bozorova Zarnigor Mo’minovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article presents a classroom-based study that explores how scaffolding method, peer collaboration, and debate-driven instruction can help upper secondary ESL learners in mastering argumentative writing and speaking abilities. The target groups are 10th and 11th grade students in a specialized English-focused public school in Uzbekistan, with learners ranging from B2 to C1 on the CEFR scale. The lesson plan integrates receptive (reading and listening) and productive (writing and speaking) skills, focusing on a discussion-centered topic: Should students be allowed to use mobile phones in school? To cover mixed proficiency levels in the class, the teacher uses differentiated scaffolding strategies such as sentence framework, vocabulary banks, guided reading, and structured group debates. The lesson culminates in a formal writing task helped by planning sheets and checklists. The findings highlight the importance of providing well-formed linguistic support, enhancing critical thinking through debate, and integrating real-world tasks that focus academic language use. The study shows how aligning scaffolding with collaborative learning can help learners’ confidence and proficiency in persuasive discourse.